2011
DOI: 10.1111/j.1755-0238.2011.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in response to ‘reduced input’ spray programs for powdery mildew and botrytis identified through whole-of-block experimentation

Abstract: Background and Aims:  Previous work has highlighted the utility of the whole‐of‐block approach to viticultural experimentation. Here, we use this approach as a means of evaluating alternative spray programs for managing two economically important grapevine diseases at commercial scale. Methods and Results:  Two experiments were conducted in vineyards in the Coal River and Rokeby districts of Tasmania. The first, carried out in a 4.5 ha vineyard planted to Vitis vinifera L. cv. Pinot Noir, sought to evaluate fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…LAWES & BRAMLEY, 2012), spatially distributed plots (WHELAN et al, 2003) or using highly replicated designs (e.g. PANTEN et al, 2010;BRAMLEY et al, 2011a) covering the entire management unit (Figure 5b) using the tools of PA for their design and establishment. Whichever approach is used, the underlying variation in the trial site is used as an experimental tool such that when the experiment is analysed using appropriate spatial analysis, spatial variability in the treatment response and in the statistical significance of treatment effects can be determined.…”
Section: A Focus On Crop Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…LAWES & BRAMLEY, 2012), spatially distributed plots (WHELAN et al, 2003) or using highly replicated designs (e.g. PANTEN et al, 2010;BRAMLEY et al, 2011a) covering the entire management unit (Figure 5b) using the tools of PA for their design and establishment. Whichever approach is used, the underlying variation in the trial site is used as an experimental tool such that when the experiment is analysed using appropriate spatial analysis, spatial variability in the treatment response and in the statistical significance of treatment effects can be determined.…”
Section: A Focus On Crop Qualitymentioning
confidence: 99%
“…Part (a), which shows a 7 ha vineyard, seeks to illustrate how the results of a small plot trial could be compromised by the underlying variation -illustrated here by a yield map. A potential solution to this is shown in (b) which shows an experiment conducted over an entire 2.4 ha vineyard (Bramley et al, 2011a). The objective was to assess the effects of the timing of spray application (either flowering or pre-bunch closure; PBC) on the incidence of botrytis.…”
Section: A Focus On Crop Qualitymentioning
confidence: 99%
“…This calls into question the utility of plot‐based experiments as a basis for viticultural decision making or the development of management recommendations. In this, and the other papers in this series (Panten and Bramley 2011, Bramley et al. 2011a), we seek to explore and demonstrate a solution to this problem, which is provided by the whole‐of‐block or ‘landscape scale’ (Bishop and Lark 2006, Panten et al.…”
Section: Introductionmentioning
confidence: 99%
“…2010) approach. Thus, in experiments in which entire management units were used for the experiment, rather than small plots, alternative vineyard floor covers (Panten and Bramley 2011) and reduced input spray programs (Bramley et al. 2011a) were evaluated in such a way that the inherent variability of the vineyard was used both as an experimental tool and also an aid to understanding treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…Bramley et al . () investigated the spatial distribution of BBR severity and found that mean severity for a given vineyard block (2·4 ha) was heavily influenced by an increase in severity in particular areas within the vineyard, while severity in the rest of the block did not increase at the same rate. These findings support the hypothesis that polycyclic secondary infection may not be a necessary mechanism for increasing BBR severity over time.…”
Section: Discussionmentioning
confidence: 99%